Complex-Valued Flatness Grid-Feeding Controller for CSI-Based Grid- Tied Converters - Gomez Jorge, Sebastian; Solsona, Jorge A.; Aguado Peralta, Yoandri; Fantino, Roberto; Busada, Claudio A. (Journal of Electronics and Electrical Engineering, 2026)
This paper presents a non-linear controller for a grid-connected power electronics converter working in grid-following mode. The topology to be controlled consists of a current source inverter fed by a dc power source through an inductive DC-link, and connected to the grid via a capacitive-inductive output filter. This results in a system that allows converting the power from the input source into a controlled three-phase ac output current that is injected into the grid. To control this system, a complex-valued flatness-based strategy is designed. The performance of the proposed control system is illustrated through simulation results.